Design and Construction of Traditional Fishing Boat in Jepara in the Context of Cultural Ecology: The Implication as Arts Learning Resources - Sugiarto, Eko; Triyanto, Triyanto; Mujiyono, Mujiyono (Universitas Negeri Semarang, 2020)
The existence of a traditional fisherman community in Jepara is proven based on the system of equipment or technology of fishing vessels. As part that is familiar with the life of the fishing community, this phenomenon is very interesting as well as important to be studied more deeply in the context of the north coast Javanese sub-culture. Based on that, this study aims to explain: (1) the design of fishing boat construction as a representation of the technology system of traditional fishing communities in Jepara, (2) the ecological aspect of the north coast Javanese sub-culture includes the process of creating traditional fishing boat in Jepara communities, and (3) wisdom potential in traditional ship design as learning resources. This study uses a qualitative approach with case study design. The data is collected through interviews, observations and document reviews, and analyzed by using flow mode. The results of the study will provide an empirical explanation of the construction design and boat creation technology in the ecological perspective of the north coast Javanese sub-culture. Traditional ship design in Jepara is potential as learning resources to create the value of cooperation, openness,Ã‚Â communication and religious.